INDONESIA'S ROLE IN THE CORAL TRIANGLE INITIATIVE TO MAINTAIN SEAFOOD SECURITY AMID CLIMATE CHANGE FROM THE PERSPECTIVE OF LIBERALISM - Arifah Nursalsabila; Darin Nafisa Mayumi Puri Ahmanto; Nandratul Jariyah; Dwi Ardiyanti (Proceedings International Indonesia Conference on Interdisciplinary Studies, 2025)
Climate change has brought significant impacts on marine ecosystems and global food security, especially for maritime countries like Indonesia. In facing this challenge, Indonesia is actively involved in the Coral Triangle Initiative (CTI), a regional multilateral framework that aims to conserve marine biodiversity and strengthen sustainable management of marine resources. This research analyzes Indonesia's role in the CTI as a strategy to maintain national seafood security amid the climate crisis, using a liberalism theory approach. This research uses a descriptive qualitative approach with literature study method as the main data collection technique and case study as the data analysis technique. This study aims to analyze Indonesia's role in the Coral Triangle Initiative (CTI) in maintaining seafood security amid climate change, based on the perspective of liberalism. The results of this study show that Indonesia positions the Coral Triangle Initiative as a means of multilateral cooperation in line with the principles of liberalism, by emphasizing the importance of international collaboration, environmental diplomacy, and local capacity building in maintaining seafood sustainability. This initiative plays a role not only in conserving marine ecosystems, but also in strengthening food security through inclusive and cooperation-based resource governance. Thus, Indonesia's involvement in the CTI demonstrates that the principles of liberalism can foster effective regional collaboration in facing the climate change crisis and maintaining seafood sustainability.